Biomimetics of throwing at basketball - Merticaru, E; Budescu, E; Iacob, R M (IOP conference series. Materials Science and Engineering, 2016)
The paper deals with the inverse dynamics of a kinematic chain of the human upper limb when throwing the ball at the basketball, aiming to calculate the torques required to put in action the technical system. The kinematic chain respects the anthropometric features regarding the length and mass of body segments. The kinematic parameters of the motion were determined by measuring the angles of body segments during a succession of filmed pictures of a throw, and the interpolation of these values and determination of the interpolating polynomials for each independent geometric coordinate. Using the Lagrange equations, there were determined the variations with time of the required torques to put in motion the kinematic chain of the type of triple physical pendulum. The obtained values show, naturally, the fact that the biggest torque is that for mimetic articulation of the shoulder, being comparable with those obtained by the brachial biceps muscle of the analyzed human subject. Using the obtained data, there can be conceived the mimetic technical system, of robotic type, with application in sports, so that to perform the motion of ball throwing, from steady position, at the basket.